2019
DOI: 10.1051/bioconf/20191202015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure on selected red wine quality parameters

Abstract: The aim of this work was to examine the possible use of High Hydrostatic Pressure (HHP) as an alternative method for wine preservation, which could also lead to the production of wines with reduced amounts of SO2. For this purpose, red wine samples containing 0 ppm, 30 ppm, 60 ppm and 100 ppm of sulphur dioxide (SO2) were subjected to pressure of 350 MPa for 10 min at 8 ∘C. A second set of samples containing only SO2 was used as control. Colour parameters, acetic acid, total anthocyanin and phenolic contents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This pyruvic acid adducts, non-analyzed in this work are also precursors of highly polymerized anthocyanins with different color ranges which may be of interest from an industrial point of view [19]. Christofi et al [20] demonstrated that HHP influenced the phenolic composition of red wines after 4 months of storage. The lower content of total phenols and monomeric anthocyanins observed in the pressurized samples after 6 months of storage was probably due to an increase of condensation and oxidation reactions.…”
Section: Phenolic Profilementioning
confidence: 86%
“…This pyruvic acid adducts, non-analyzed in this work are also precursors of highly polymerized anthocyanins with different color ranges which may be of interest from an industrial point of view [19]. Christofi et al [20] demonstrated that HHP influenced the phenolic composition of red wines after 4 months of storage. The lower content of total phenols and monomeric anthocyanins observed in the pressurized samples after 6 months of storage was probably due to an increase of condensation and oxidation reactions.…”
Section: Phenolic Profilementioning
confidence: 86%